Advances in virus research. - Maramorosch, Karl; Murphy, Frederick A. (Advances in virus research, 2013)
Published since 1953, Advances in Virus Research covers a diverse range of in-depth reviews providing a valuable overview of the current field of virology.Key features: * Contributions from leading authorities * Informs and updates on all the latest developments in the field.